Immunometabolism, extracellular vesicles and cardiac injury - Omoto, Ana C. M.; do Carmo, Jussara M.; da Silva, Alexandre A.; Hall, John E.; Mouton, Alan J. (Frontiers in Endocrinology, 2024)
Recent evidence from our lab and others suggests that metabolic reprogramming of immune cells drives changes in immune cell phenotypes along the inflammatory-to-reparative spectrum and plays a critical role in mediating the inflammatory responses to cardiac injury (e.g. hypertension, myocardial infarction). However, the factors that drive metabolic reprogramming in immune cells are not fully understood. Extracellular vesicles (EVs) are recognized for their ability to transfer cargo such as microRNAs from remote sites to influence cardiac remodeling. Furthermore, conditions such as obesity and metabolic syndrome, which are implicated in the majority of CVD cases, can skew production of EVs towards pro-inflammatory phenotypes. In this mini-review, we discuss the mechanisms by which EVs may influence immune cell metabolism during cardiac injury and factors associated with obesity and the metabolic syndrome that can disrupt normal EV function. We also discuss potential sources of cardio-protective and anti-inflammatory EVs, such as brown adipose tissue. Finally, we discuss implications for future therapeutics.